WATER IN THE EARLY EARTH - Marty B.; Yokochi R. (My University, 2006)
The origin of water is a long standing problem that has fascinated generations of philo-sophers and scientists since the dawn of humanity. It has to do with processes that took place in the nascent solar system, but, unfortunately, we lack record of what really happened during this dark age. On Earth, the tectonic activity has erased completely any record dating back from this period, and the oldest rocks preserved on Earth crystallized about 600 Ma after start of solar system condensation (ASSC). What we observe today does not represent necessarily what was present when the solar system formed, and it may well be possible that the true water ancestors could have had chemical and isotopic characteristics that are not observed in any reservoir of the present-day solar system. However, the extraterrestrial objects that escaped planetary differentiation (chondrites, comets, interplanetary dust) are probably the best available precursor candidates for the source of volatile elements in Earth. In this context, the nature of such potential contributions can be estimated in view of chemical and isotopic mass balance, taking into account astrophysical and/or thermodynamic constraints on planetary system formation.